Pendidikan Anti Korupsi Berpendekatan Klarifikasi Nilai Di Sekolah Dasar - Al Darmono Al Darmono (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2017)
Corruption seems to have been entrenched among the people of Indonesia. Events of corruption almost every day is preached in mass media. Although all efforts to eradicate continue to be done but the case of corruption is still not reduced. Corruptive behavior is actually bad impact not only economic system but also the system of democracy, politics, law, government and so forth. Based on the adverse impacts, corruption should continue to improve. Efforts to eradicate corruption are not only through the provision of sanctions and punishment for the perpetrators but should be carried out early preventive measures through anti-corruption education in Elementary School. One alternative of anti-corruption education in Primary School is through Value Clarification approach. The approach is an approach that places emphasis on helping students learn their own feelings and actions, to enhance their own values. This approach is considered effective for education in a democratic world, such as Indonesia.